INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA KEGIATAN EKSTRAKURIKULER ROHANIAH ISLAM DALAM MEMBINA KARAKTER PESERTA DIDIK DI SMA NEGERI 1 AIR PUTIH KECAMATAN AIR PUTIH KABUPATEN BATU BARA - Nur Aini (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
The purpose of this study is to describe the implementation of theinternalization of Islamic religious values through Islamic spiritualextracurricular activities in SMA Negeri 1 Air Putih , and to describe thesupporting factors and obstacles. From the results of the study it can beconcluded that the process of internalizing Islamic religious SMA Negeri 1 Air Putih  Islamic spiritual extracurricular activities in high school uses two ways namely direct (exemplary, habituation, supervision, advice, andpunishment) and indirect (classroom learning). And there are four stages,namely giving knowledge, understanding, refraction, and internalization.Supporting factors include the majority of students coming from religiousand active families studying at the diniyah madrasa, the availability ofinfrastructure and other supporting equipment. While the inhibitingfactor is each student has a different background, some teachers who areless active in participating in Islamic spiritual extracurricular activitiesand the saturation of students in participating in Islamic spiritualextracurricular activities. INTERNALISASI NILAI-NILAI PENDIDIKAN AGAMA ISLAMPADA KEGIATAN EKSTRAKURIKULER ROHANIAH ISLAM DALAM MEMBINA KARAKTER PESERTA DIDIK DI SMANEGERI 1  AIR PUTIH KECAMATAN AIR PUTIH KABUPATEN BATU BARA